Effects of the Covid- 19 Pandemic and its Attendant Lockdown Policy on the Economy of Plateau State - Dr. Yohanna Gyang Jugu; Dr. Mary Ada Ogenyi; Tosin D. Bodunde; Dr. Abubakar Saidu (International Journal of Engineering and Management Research, 2021)
The Continuous Decline In Revenue Base Of The Nation Has Remain A Matter Of Serious Concern Among Researchers And Government, Due To Challenges Arisen From The Covid – 19 Pandemic. In The Light Of This, The Study Was Set Out To Empirically Examine The Effects Of Covid – 19 Lockdown On The Internally Generated Revenue Of Plateau State. To Achieve This Objective, Systematic Review And Meta-Analysis, Combined With An Exploratory Research Design Approach Were Employed And Adopted By The Researchers, And A Sample Of 76 Respondents Was Taken From The Population Of Staff Of The Plateau State Internal Revenue Service With Specific Focus On Those That Are Directly Responsible For The Collection Of Taxes. To Analyse The Data, Both Independent T – Test And Logit Binary Regression Model Were Used To Test The Hypotheses Of This Study. Arisen From The Analysis, The Study Revealed That: There Is Significant Difference Between Revenue Generated Before And During Covid-19 Lockdown In Plateau State; And Covid - 19 Lockdown Has Significant Adverse Effect On Internally Generated Revenue (Igr). Based On The Findings, The Following Recommendations Were Made: Government Of Plateau State Should Ensure That Business Activities Are Continuing Through Digitalised System And That The Government Should Link Tax Identification Numbers (Tin) To Online Business Activities So As To Guarantee Continued Internally Revenue Generation For The State; Government Should Train Their Staff On The Use Of Ict, Especially In The Area Of Revenue Collection; And Staff Of Ministries, Departments And Agencies (Mdas) Should Ensure That Sharp And Dubious Practices Are Properly Checked To Allow For The Free Flow Of Ict System In Revenue Collection.